The Effectiveness of ChatGPT-Assisted Project-Based Learning in Enhancing Critical Thinking Skills among Pre-Service Teachers - Andri Candra (Suria Academic Press, 2026)
The integration of Generative Artificial Intelligence (GenAI) into higher education has created new opportunities to enhance student-centered learning and foster higher-order thinking skills. However, empirical evidence regarding the effectiveness of ChatGPT-assisted Project-Based Learning (PBL) in teacher education remains limited. This study investigated the effectiveness of ChatGPT-assisted PBL in improving the critical thinking skills of pre-service teachers. A quasi-experimental pretest–posttest control group design was employed involving 68 pre-service teachers enrolled in an Educational Technology course. Participants were assigned to an experimental group (n = 34), which received ChatGPT-assisted PBL, and a control group (n = 34), which received conventional PBL. Critical thinking was assessed using a validated performance-based instrument based on Facione’s six dimensions. Data were analyzed using descriptive statistics, Shapiro–Wilk and Levene’s tests, paired and independent samples t-tests, normalized gain (N-Gain), and Cohen’s d. The findings revealed that the experimental group achieved significantly higher critical thinking scores than the control group (t = 7.36, p < 0.001), with a high N-Gain (0.71) compared to a moderate gain (0.43) in the control group. The intervention also demonstrated a large practical effect (Cohen’s d = 0.97), particularly improving students’ analytical reasoning and explanatory abilities. These findings suggest that integrating ChatGPT into Project-Based Learning effectively promotes critical thinking by supporting inquiry, evidence-based reasoning, and reflective learning. The study highlights the potential of Generative AI as a pedagogical partner in preparing future teachers for AI-enhanced educational environments.